Breaking Down Barriers to Second Language Learning: Understanding Factors and Strategies for High School Students in Guyana - Lewis, André (International Journal of Language and Literary Studies, 2024)
This study aims to illustrate the challenges that prevent most high school students in Guyana from showing any interest and participating in learning a second language. The study showed a number of socio-cultural, economic and institutional constraints which are generally exposed by combining 60 SLA questionnaires with interviews administered to SS3 students who did not continue with the learning of a second language after undergoing their third cycle at grade nine. The results expose nuanced student perspectives and structural impediments, offering practical recommendations to inform the strategies of policymakers, educators’ et al at school- (micro) as well as the system-level (macro). The reforms are intended to reduce current barriers and consequently create a more favourable environment for second language learning among Guyanese high school students.